Dynamic computer animation of a human arm - Zhang, Min (2009)
The goals of this thesis are to investigate different dynamics formulations for the computer animation of a human arm and find an efficient control strategy to control the motion of a human arm. In this thesis, we compare different formulations used in previous research. We derive a closed-form formulation based on the D' Alembert dynamics formulation to represent our human arm with 3 degrees of freedom. Another recursive formulation based on the Newton-Euler formulation is also investigated and used to represent our human arm with 6 degrees of freedom.